Desenvolvimento e validação de tecnologia educativa leve-dura, sob o formato de aplicativo multimídia para plataforma móvel, para favorecimento a garantia do dever de cuidado com idoso no município de mossoró-rn - Duarte, Ulissea de Oliveira (2018)
There is concern about active aging in the face of the senility of the population, especially in guaranteeing dignified aging and access to the rights enshrined in national legal instruments. This study aimed to develop and validate a light-hard technology, in the format of a multimedia application in mobile platform, having as scope concepts and procedures related to guaranteeing the duty to care for the elderly. A technological, descriptive, longitudinal research was carried out in the modality of development of technological, qualitative-quantitative production from June 2017 to March 2018. Phases were developed. Phase 1 - situational diagnosis - conducted survey from the VHL and Science Direct guided by the question: What information is available on guarantee of the duty of care of the elderly? Portuguese, English or Spanish studies were included, complete access was available and a semi-structured interview was carried out with all professionals from the courts of Mossoró / RN and with health and social care professionals working in the municipal network of Mossoró / RN selected through of non-probabilistic, intentional sampling, through indication by the Coordination of Basic Attention of the municipality. The data were analyzed through the Bardin content analysis. Phase 2 - development of prototypes (drafting of illustrations, layout, design and texts) and Phase 3 - validation (apparent and content) through experts (lawyers, health professionals and communication) who analyzed organization, writing style, appearance and motivation to use technology through the Delphi technique using Likert scale. Data were analyzed using the Yates corrected chi-square and Kappa index. The results of phase 1 revealed a shortage of studies in the area with only 02 studies in the VHL and 08 in Science Direct. The interview of professionals revealed three key points: duty of care of the elderly (regulation health care); violation of the duty of care (family responsibility and omission of the state) and existing action to guarantee compliance with the duty of care of the elderly (absence of specific action with the elderly). In phase 2 was created the app called GruDaDO - Guarantee of rights of the elderly was developed through the website Fabapp (https://fabricadeaplicativos.com.br/, containing 5 tabs (duty to care for the elderly, rights of the elderly, violence in the environment In phase 3, the evaluators judged the content / relevance (mean = 3.3 ± 1.7), conceptual adequacy (mean = 3.7 ± 1.2 (mean = 4 ± 0.0), clarity and language (mean = 4.1 ± 0.3), comprehension of texts (mean 4.2 ± 0.5), objectivity (mean = 4, (Mean = 4.1 ± 0.4), illustrations (mean = 4.2 ± 0.5), image and visual composition (mean m = 3.5 ± 1.3) (p> 0.05), and that the use of multimedia resources is a differentiated tool for the promotion of the knowledge in several areas, which enables the propagation of old guarantees, which provide greater effectiveness to the right duty of care to the elderly